Creating Neighborhood in Postwar Buffalo, New York: Transformations of the West Side, 1950-1980 - (:unkn) unknown (My University, 2014)
This project reconsiders post-World War II neighborhood change by examining how various groups in Buffalo, New York conceptualized, experienced and produced the West Side as a cultural and economic artifact between 1950 and 1980. This approach offers an alternative to conceptualizing neighborhoods as bounded, natural entities and it encourages narratives that complicate the prevailing metaphor of decline in rust belt cities by illuminating other components of postwar neighborhood change than population loss and economic disinvestment. This project uses neighborhood retail as a lens through which to examine how city planners, the West Side Business Men's Club, the Federation of Italian American Societies and individual storeowners reproduced the neighborhood at multiple scales through city planning, local marketing, Columbus Day celebrations, and personal decisions. As the logics of those practices changed alongside shifting social and economic contexts in the depopulating, deindustrializing city, these social agents negotiated the West Side as both a tangible place and an abstract imaginary. While the place-based City and businessmen's club promoted the area as a commercial destination, individual storeowners connected West Side stores to businesses networks that extended across the city. At the same time, the Federation recast the West Side as the "old neighborhood," and a launching point for Italian American upward mobility in the region. The first three chapters concentrate on retail patterns at different scales of neighborhood production. The first chapter examines commercial areas of the West Side as sites of city planning intervention, the second chapter considers how the local business organization constructed the Grant-Ferry area as a defined entity through marketing and events, and the third chapter uses the stories of three individual business owners to show how the singular place images of the first two chapters belies personal experience of the same shopping area on the ground. The final chapter shifts to the Federation of Italian American Societies' production of a regional Italian identity that casted the West Side as a place of the past, echoing the sentiments of former West Siders who identified the Grant-Ferry area as an idealized but bygone center of community. Each chapter of the project highlights the Grant-Ferry area as a critical component of neighborhood identity for groups engaging the West Side's the past, present, and future as they responded to citywide and regional transformations. Together, these chapters suggest the importance of understanding neighborhood commercial areas as social and economic resources that stakeholders at multiple scales engage and transform simultaneously during periods of neighborhood change. This project contributes to a growing literature that interrogates the production of neighborhoods as emergent, ongoing processes. Getting beyond the "container" view of neighborhood reconnects postwar neighborhood change to broader urban development processes by illuminating scalar interconnections that remain obscured in those studies. This study interprets conceptualizations and uses of the West Side by examining how the groups and individuals framed neighborhood identity in planning documents, newspaper reports, maps, city directories, and interviews. Each point of view invoked the neighborhood through different temporal and functional associations, and implicated a different audience of neighborhood identity. This study suggests that using this approach, scholars of urban history and urban studies can better understand American neighborhoods as products of the same forces and contexts that produced other postwar landscapes rather than as sites or survivors of postwar urban decline. This project is also relevant to contemporary neighborhood revitalization efforts on the West Side of Buffalo because it suggests that the "rediscovery" narrative accompanying new investment is problematic in the same ways as the "decline" narrative commonly used to frame the last three decades; each explanation centers on a limited cast of stakeholders and severs the historical continuity of the processes that define places.
Keywords: Neighborhood; Place; Placemaking; Practice; Rust Belt